Antenatal models of care for women with gestational diabetes mellitus: Vignettes from an international meeting. (10th March 2020) - Sina, Maryam; Cade, Thomas J.; Flack, Jeff; Nolan, Christopher J.; Rajagopal, Rohit; Wong, Vincent; Burcher, Linda; Barry, Alison; Gianatti, Emily; McCarthy, Ana; McNamara, Catharine; Mickelson, Marina; et al.
Abstract : Background: Gestational diabetes (GDM) is one of the commonest pregnancy complications and is placing an increasing burden on diabetes and obstetric resources. Aims: To describe different antenatal models of care that have developed to address the increasing proportion of pregnancies complicated by GDM. Materials and Methods: Narrative review with thematic analysis from 15 volunteer antenatal diabetes in pregnancy services from Australia and New Zealand identified through a national diabetes organisation. Main outcomes were approaches to patient education, medical nutrition therapy (MNT), ongoing management and escalation of therapy for women with GDM. Results: All clinics provided at least one group education and one MNT session within 1–2 weeks of GDM diagnosis. Women from culturally and linguistically diverse communities usually required 1:1 education. Ongoing management of women with GDM was through either all women being seen in the GDM clinic, a step‐up approach (ongoing management by the primary antenatal team with diabetes team referral if self‐blood glucose monitoring (SBGM) or insulin therapy dosage criteria are reached) or step‐down approach (ongoing management by the diabetes team with step‐down to the primary antenatal team if SBGM criteria are reached). Telehealth was used to reduce the burden of clinic attendance, particularly in rural areas. Conclusions: Increasing numbers, earlier diagnoses, the need to provide care to women in rural, remote areas, and cultural/language differences, have generated a range of different antenatal models of care, allowed better workload accommodation and probably reduced costs. Randomised controlled trials of different models of care, with associated health economic analyses, are urgently needed.